The optimization of chromatographic conditions for testing of Antarctic region hydrobionts tissue extracts - D.V. Gladun; T.B. Vovk; N.G. Raksha; O.M. Savchuk; L.I. Ostapchenko (Ukrainian Antarctic Journal, 2015)
Conditions for providing optimal fractionation of tissue extracts bу gel filtration chromatography were selected. Further enzyme-electrophoretic analysis of the obtained protein fractions revealed the presence in extract of Actinaria and Sterechinus neumayer the active forms of the enzymes.